Amorphous/crystalline heterojunction interface driving the spatial separation of charge carriers for efficient photocatalytic hydrogen evolution. (October 2022) - Zhang, Lijun; Wu, Youlin; Li, Junke; Jin, Zhiliang; Li, Youji; Tsubaki, Noritatsu
Abstract: The basic energy conversion in the photosynthetic system is the process of separation, transfer and utilization of photogenerated charges. Here, an amorphous/crystalline heterojunction photocatalyst with spatial separation effect is prepared by assembling graphdiyne (GDY) flakes onto MoS2 –CdS nanodumbbells. Graphdiyne flexible flakes were synthesized via a Glazer-Hay coupling reaction using cuprous bromide (CuBr) as a catalyst. One-dimensional MoS2 –CdS nanodumbbells with symmetrical amorphous MoS2 tips can effectively promote the separation of electrons and holes in space, attracting photogenerated electrons to move along the one-dimensional nanorods. The GDY two-dimensional flexible sheet, which can promote the outward movement of photogenerated holes and isolate the surface oxidation sites, is like a "protective suit" on the dumbbell structure, thereby improving the resistance to photocorrosion. The MoS2 –CdS/GDY-10% composite photocatalyst shows the highest photocatalytic water splitting activity of graphdiyne applied to photocatalytic systems so far, and the highest hydrogen production rate can reach 17.99 mmol g −1 h −1, which is 161 times that of pure CdS. The conversion efficiency of solar energy to hydrogen energy can reach 3.2%. The highest quantum efficiency is 6.48% at 450 nm. The synergistic effect of the special spatial structure and the amorphous/crystalline heterojunction can significantly reduce the recombination of electron-hole pairs and prolong the lifetime of photogenerated carriers. This work inspires the construction of graphdiyne-based photocatalysts with high activity and high stability, demonstrating the promising future of graphdiyne for photocatalytic water splitting. Graphical abstract: Image 1 Highlights: Synthesis of flexible graphdiyne flakes via Glazer-Hay coupling reaction in the presence of CuBr. Graphdiyne transfer and isolate surface oxidation sites for improved photocorrosion resistance. Nanodumbbell structure has sterically separated active sites to facilitate the separation of e − and h + . Amorphous/crystalline heterojunctions inhibit charge carrier recombination. Shows the highest water splitting activity of the graphdiyne-based photocatalysts to date.